Best Practice of Moodle Implementation for E-Learning: A Perspective of Public University Lecturers - Yunos, Nasruddin; Muslim, Nazri; Hussain, Afifuddin Husairi; Hasim, Nur Asmadayana; Nazri, Nurul Syakirah; Hamsan, Muhamad Hafiz (Journal of Ecohumanism, 2024)
Moodle is a popular open-source learning management system (LMS) used for online learning and course management. It provides educators with tools to create online courses, manage learning content, track student progress, conduct assessments, and facilitate communication and collaboration among students and instructors. Moodle is widely used in educational institutions, corporate training settings, and various other learning environments around the world. The aim of this article was to study the best practices for implementing Moodle in e-learning, as perceived by public university lecturers. This study employed a qualitative approach, utilizing Focus Group Discussions (FGDs) among lecturers from public universities. All data were meticulously transcribed and subsequently analyzed thematically. The results show, experts agreed that three best practices were i) Optimizing the task of e-learning manager, ii) Utilize the restriction option to uphold student integrity and, iii) Implementing regular data backups. Therefore, this study enriches the field by providing practical recommendations for implementing Moodle, drawing from the insights of public university lecturers.